Differences in Physical Fitness Level Students studying Volleyball and Football Industrial Engineering Study Program UPN "Veteran" Yogyakarta - Sumintarsih, Sumintarsih; Saptono, Tri; Mustofa, Hanafi (Jurnal Indonesia Sosial Sains, 2024)
The objectives of this study are The effect of volleyball on the physical fitness level of UPN "Veteran" Yogyakarta Industrial Engineering study program students, the influence of soccer on the physical fitness level of students of the Industrial Engineering study program UPN "Veteran" Yogyakarta, the difference in the influence of volleyball and soccer on the level of physical fitness of students of the industrial engineering study program UPN "Veteran" Yogyakarta. This research uses an experimental method. The subjects of this study consisted of students of the UPN "Veteran" Yogyakarta industrial engineering study program who took Sports II courses in volleyball and football. The sampling technique is a targeted random sample, with a sample of 25 participants in each group. This research data analysis method uses a t-test. The normality test (Kolmogurov-Smirnov, α = 0.05) and the variance homogeneity test (Levene test, α = 0.05) were used to test the data analysis requirements. The results of the research are as follows: Football has an influence on improving the physical fitness of industrial engineering students at UPN "Veteran" Yogyakarta, with an average pre-test result of 34,748 post-test results of 37,864 students, with an average increase in the number of students of 3,121 cases showing that physical fitness increases through football. 2) Volleyball has an effect on the physical fitness of industrial engineering students UPN "Veteran". Yogyakarta It can be seen from the average score, pre-test results of 27,160, and post-test results of 29,120, the average increased by 1.96. This means that physical strength increases through volleyball. 3) There is a significant difference in influence between volleyball and football, significance at a significance level of 5% of 0.036 and a T-count of -2.152.